PLANNING FOR THE RAPIDLY EMERGING DIGITAL OR - Swart, Rob (Operating Room Nurses Association of Canada Journal, 2005)
Nurses working in today’s operating room environments are faced with new technologies being added as the trend toward the digitalization of ORs becomes a reality. Many hospitals across the country are currently undergoing renovations to include updated equipment. This means nurses must adapt to new systems and become familiar with the driving forces behind the trend and how it will affect their daily work. Here, the author explores why digital ORs are increasingly becoming the norm and what today’s nurses need to understand in order to be effective in this emerging environment.